The Role of L-DOPA on Melanization and Mycelial Production in Malassezia Furfur - Youngchim, Sirida; Nosanchuk, Joshua D.; Pornsuwan, Soraya; Kajiwara, Susumu; Vanittanakom, Nongnuch (PLOS ONE, 2013)
Melanins are synthesized by organisms of all biological kingdoms and comprise a heterogeneous class of natural pigments. Certain of these polymers have been implicated in the pathogenesis of several important human fungal pathogens. This study investigated whether the fungal skin pathogen Malassezia furfur produces melanin or melanin-like compounds. A melanin-binding monoclonal antibody (MAb) labelled in vitro cultivated yeast cells of M. furfur. In addition, melanization of Malassezia yeasts and hyphae was detected by anti-melanin MAb in scrapings from patients with pityriasis versicolor. Treatment of Malassezia yeasts with proteolytic enzymes, denaturant and concentrated hot acid yielded dark particles and electron spin resonance spectroscopy revealed that these particles contained a stable free radical compound, consistent with their identification as melanins. Malassezia yeasts required phenolic compounds, such as L-DOPA, in order to synthesize melanin. L-DOPA also triggered hyphal formation in vitro when combined with kojic acid, a tyrosinase inhibitor, in a dose-dependent manner. In this respect, L-DOPA is thought to be an essential substance that is linked to both melanization and yeast-mycelial transformation in M. furfur. In summary, M. furfur can produce melanin or melanin-like compounds in vitro and in vivo, and the DOPA melanin pathway is involved in cell wall melanization.